Biodiversity as a Tool for the Integrated Teaching of Natural Sciences and Mathematics - Esquivel Martín, Tamara; Bravo-Torija, Beatriz; Pérez Martín, José Manuel (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2019)
Initial teacher training should consider the introduction of dynamics from an interdisciplinary approach to promote the development of scientific/mathematical skills in everyday contexts. This study analyses pre-service Primary School teachers’ performance in scientific/mathematical skills through a teaching proposal that aims to classify and interpret an unidentified sample of shells and analyse the limitations encountered by the students. The analysis of the report’s content shows that the general and communicative skills are developed by most of the groups, while there’s has been a greater difficulty to develop the research skills. The educational implications of this are eventually discussed.